Vitamin C enhances co-localization of novel TET1 nuclear bodies with both Cajal and PML bodies in colorectal cancer cells - Nour El Osmani; Corinne Prévostel; Laurence Picque Lasorsa; Mohammad El Harakeh; Zeina Radwan; Hiba Mawlawi; Marwan El Sabban; Margret Shirinian; Zeina Dassouki (Epigenetics)
Deregulation of ten-eleven Translocation protein 1 (TET1) is commonly reported to induce imbalances in gene expression and subsequently to colorectal cancer development (CRC). On the other hand, vitamin C (VitC) improves the prognosis of colorectal cancer by reprogramming the cancer epigenome and limiting chemotherapeutic drug resistance events. In this study, we aimed to characterize TET1-specific subcellular compartments and evaluate the effect of VitC on TET1 compartmentalization in colonic tumour cells. We demonstrated that TET1 is concentrated in coarse nuclear bodies (NB) and 5-hydroxymethylcytosine (5hmC) in foci in colorectal cancer cells (HCT116, Caco-2, and HT-29). To our knowledge, this is the first report of a novel intracellular localization profile of TET1 and its demethylation marker, 5hmC, in CRC cells. Interestingly, we found that TET1-NBs frequently interacted with Cajal bodies, but not with promyelocytic leukaemia (PML) bodies. In addition, we report that VitC treatment of HCT116 cells induces 5hmC foci biogenesis and triggers 5hmC marks to form active complexes with nuclear body components, including both Cajal and PML proteins. Our data highlight novel NB-concentrating TET1 in CRC cells and demonstrate that VitC modulates TET1-NBs’ interactions with other nuclear structures. These findings reveal novel TET1-dependent cellular functions and potentially provide new insights for CRC management.